2010
DOI: 10.5860/crln.71.1.8302
|View full text |Cite
|
Sign up to set email alerts
|

Social media: A guide for college and university libraries

Abstract: S ocial media is a powerful new form of communication. The number of users on poular social media sites is growing at exponential rates. Facebook has more than 300 million active users, 1 which rivals the population of the United States. From February 2008 to February 2009, Twitter experienced 1,382% growth rate. 2 Millions of people are using these tools as part of their everyday lives for both work and play. Because of the ubiquity of social media use, academic libraries can leverage these communication tool… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(39 citation statements)
references
References 0 publications
1
37
0
1
Order By: Relevance
“…Social media, like any other technology, takes a bit of time and play to learn. Usually librarians have limited time to learn how to use social media, which is not given priority (Burkhardt, 2010). In addition, the study also found that interactive features of Social media and willingness are not enough to remove all barriers for knowledge sharing.…”
Section: Rq5 What Barriers Do They Feel Exist For Knowledge Sharing mentioning
confidence: 93%
“…Social media, like any other technology, takes a bit of time and play to learn. Usually librarians have limited time to learn how to use social media, which is not given priority (Burkhardt, 2010). In addition, the study also found that interactive features of Social media and willingness are not enough to remove all barriers for knowledge sharing.…”
Section: Rq5 What Barriers Do They Feel Exist For Knowledge Sharing mentioning
confidence: 93%
“…This is especially true for public libraries. The bulk of literature on social media marketing is produced by professional librarians in service-oriented publications in the form of how-to articles, manuals, and similar guides (Burkhardt 2010;Glazer 2012;Hardin, Klug, and Williams 2012;Salomon 2013;Solomon 2013). Case studies of individual libraries as exemplars of best practices in social media are also common (Cahill 2011;Dempsey 2012;Ezeani and Igwesi 2012;Dankowski 2013;Salomon 2013 Not only do librarians need to know how to use social media to reach patrons, but they also must understand what types of patrons they are reaching and what services appeal to social media savvy patrons (Horn 2011).…”
Section: Running Head: Facebooking Itmentioning
confidence: 99%
“…This can be done through online social networking. Burkhardt 4 affirmed that online social networking tools create an avenue which academic libraries can explore to market its products and services. Burkhardt also noted that the versatility of online social networking, made in evitable for libraries to utilise and communication with faculty, staff, and students in new ways.…”
Section: Sn In Marketing Library Activitiesmentioning
confidence: 99%
“…Social networking in libraries will promote adequate information access, sharing, dissemination which are core functions of academic libraries. Chu & Meulemans 3 , Burkhardt 4 , Robinson, Aggarwal & Buggarapu 5 see online social networking as an effective tool for organisational productivity and service delivery. In china, social media is increasingly an important force for defining taste and driving purchases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation